Aggressiveness and social skills in elementary school children in the I.E. 10020, Zaña 2016 - Hernández Quispe, Estrellita del Carmen (2017)
The present study entitled "Aggressiveness and social skills in elementary school children of Educational Institution 10020, Zaña 2016", aims to verify the level of significance between the level of aggressiveness and social skills in students; the objective is to determine the level of the relationship between aggression and social skills. The type of research is descriptive correlational, with non-experimental design. The population is made up of 410 students and the sample was established with children who have ages between 10 and 12 years, and that by probabilistic sampling, was taken into account of 52 students. It was concluded that there is no relationship between aggression and social skills.